2012
DOI: 10.1097/acm.0b013e31826d726b
|View full text |Cite
|
Sign up to set email alerts
|

Are Race, Ethnicity, and Medical School Affiliation Associated With NIH R01 Type 1 Award Probability for Physician Investigators?

Abstract: Purpose To analyze the relationship among NIH R01 Type 1 applicant degree, institution type, and race/ethnicity, and application award probability. Method The authors used 2000–2006 data from the NIH IMPAC II grants database and other sources to determine which individual and institutional characteristics of applicants may affect the probability of applications being awarded funding. They used descriptive statistics and probit models to estimate correlations between race/ethnicity, degree (MD or PhD), and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 10 publications
2
77
0
Order By: Relevance
“…1,2,4,5,9–13 The ten variables include four research activities (participating in a research elective during medical school, authorship of a research report submitted for publication, spending at least one year during residency doing research, and receipt of a federal research fellowship [F32] grant), two academic performance measures (scores on the United States Medical Licensing Examination [USMLE] Step 1 and Step 2 Clinical Knowledge [CK]), plus medical school research intensity, degree program, debt at graduation, and specialty. We describe each of these potential mediators and our data sources in detail below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4,5,9–13 The ten variables include four research activities (participating in a research elective during medical school, authorship of a research report submitted for publication, spending at least one year during residency doing research, and receipt of a federal research fellowship [F32] grant), two academic performance measures (scores on the United States Medical Licensing Examination [USMLE] Step 1 and Step 2 Clinical Knowledge [CK]), plus medical school research intensity, degree program, debt at graduation, and specialty. We describe each of these potential mediators and our data sources in detail below.…”
Section: Methodsmentioning
confidence: 99%
“…1–3 Currently investigators from some racial/ethnic groups are less likely than others to receive research funding as independent investigators. 4 Mentored K (K01/K08/K23) career development awards are positively associated with physicians’ success in becoming federally funded independent investigators. 1,5 An evaluation of the National Institutes of Health (NIH) K award program has shown that there have been fewer Blacks, Hispanics, and Native Americans among mentored K award program applicants and awardees compared to their representation in PhD and graduating medical-school classes.…”
mentioning
confidence: 99%
“…9 The probability of being awarded R01 funding for new proposals differs by race/ethnicity, with black applicants being less successful than white applicants (including both MD and MD-PhD applicants). 32 Further research is warranted to fill the gap in knowledge about the physician-scientist career paths of female and URM MD-PhD program graduates specifically.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly encouraging because this success of CSDA alumni may indicate an increase in human subject research funding, which traditionally has had a lower likelihood of receiving funding. 24 Many factors could explain this finding. The CSDA program could truly have an impact on the research enterprise by providing flexible funds and protected time for research activities at a critical time in the development of early-career scientists.…”
Section: Transition To Independent Research Fundingmentioning
confidence: 90%